Hormones and Sex-Specific Transcription Factors Jointly Control Yolk Protein Synthesis in Musca domestica. (5th October 2009) - Siegenthaler, Christina; Maroy, Peter; Hediger, Monika; Dübendorfer, Andreas; Bopp, Daniel
Abstract : In the housefly Musca domestica, synthesis of yolk proteins (YPs) depends on the level of circulating ecdysteroid hormones. In female houseflies, the ecdysterone concentration in the hemolymph oscillates and, at high levels, is followed by expression of YP. In male houseflies, the ecdysterone titre is constantly low and no YP is produced. In some strains, which are mutant in key components of the sex-determining pathway, males express YP even though their ecdysterone titre is not significantly elevated. However, we find that these males express a substantial amount of the female variant of the Musca doublesex homologue, Md-dsx . The dsx gene is known to sex-specifically control transcription of yp genes in the fat body of Drosophila melanogaster . Our data suggest that Md-dsx also contributes to the regulation of YP expression in the housefly by modulating the responsiveness of YP-producing cells to hormonal stimuli.